Controlling the compactness and sp2 clusters to reduce interfacial damage of amorphous carbon/316L bipolar plates in PEMFCs. (12th March 2022) - Li, Hao; Xin, Yang; Komatsu, Keiji; Guo, Peng; Ma, Guanshui; Ke, Peiling; Lee, Kwang-Ryeol; Saito, Hidetoshi; Wang, Aiying
Abstract: In proton exchange-membrane fuel cells, the compactness and composition of amorphous carbon (a-C) films directly affect the interface-induced degradation of a-C-coated metallic bipolar plates, but their roles and synergistic effects are ambiguous. In this study, by changing the working pressure, the compactness and composition of a-C are adjusted, and the relationship among the plasma state, microstructure, and performance of coated 316L stainless steel are studied. Results show that, at 2 mTorr, a high ionization degree of the plasma causes high compactness (highest density 2.52 g/cm 3 ) and large sp 2 cluster size in a-C films, resulting in their best performance. At 11 mTorr, the low ionization degree causes their loose structure and large sp 2 cluster size. The possible galvanic coupling effect can result in serious interface damage and the highest Fe ions concentration of 13.05 ppm after a potentiostatic test. Thus, high compactness and large sp 2 cluster sizes should be obtained simultaneously to improve their performance. Graphical abstract: Image 1 Highlights: Quantitative analysis of the plasma state by the single Langmuir probe. Compactness of a-C films by testing their density with X-ray reflectivity method. Reveal plasma states and film compactness on corrosion resistance and conductivity.